Congenital hepatic fibrosis in Turkish children - Koçak, Nurten; Özsoylu, Şinasi; Çağlar, Melda; Göğüş, Safiye (The Turkish Journal of Pediatrics, 1986)
Twenty-four cases of congenital hepatic fibrosis are presented. There was hepatomegaly, the enlargement of the left lobe in 17 cases, splenomegaly in 18 cases, hematemesis in 7 cases, and melena in 8 cases; further there was consanguinity of the parents of 11 patients. In the liver biopsies fibrosis was more prominent in 13 patients and cystic lesions in 11 of them. It should be stressed that congenital hepatic fibrosis should be considered among the causes of portal hypertension in childhood and should be distinguished from cirrhosis.
Keywords: congenital hepatic fibrosis; portal hypertension